ANALISIS KESALAHAN KEBAHASAAN DALAM TEKS PROSEDUR TABLOID NOVA - Anggraini, Nabila Syifa; Inderasari, Elen (University of Brawijaya, 2024)
The phenomenon of language errors is still found in several tabloids, one of which is the Nova tabloid. There are still many grammatical errors found in the procedural text presented in the Nova tabloid, especially in the “Sedap Sedap” section. This study aims to explain the form of language errors in the procedural text of the Nova tabloid